Perlindungan Hukum Terhadap Gelandangan dan Pengemis di Kota Batam sebagai Akibat Implementasi Peraturan Daerah Kota Batam Nomor 6 Tahun 2002 Tentang Ketertiban Sosial - Rufinus Hotmaulana Hutauruk; Dian Eka Putri (Universitas Internasional Batam, 2021)
The presence of vagrants and beggars in Batam City is one of the problems of community welfare that is not easy to solve. Therefore, it is necessary to have a clear protection of the law against Vagrants and beggars in Batam City, not only to make efforts to combat vagrants and beggars but also to fulfill the rights of vagabonds and beggars that must be put forward by the Batam City Government. In this case, tackling the problems of vagabonds and beggars is the responsibility of the state. If you look at the contents of the 1945 Constitution of the Republic of Indonesia in Article 27 paragraph (2) which states that